Comprensión lectora y logro de aprendizaje en el área de ciencias sociales estudiantes del nivel secundaria de la Institución Educativa Nº 60080 Ramón Castilla 2023 - Sosa Campos, Graciela Marina (2024)
The research scientifically resolves the relationship that exists between reading comprehension and learning achievements in the area of social sciences in secondary level students of Educational Institution No. 60080 of the Ramón Castilla district, during the 2023 school year. In addition, it validates the existence of a significant relationship between the variables: reading comprehension and learning achievement. Reading comprehension and learning achievement, according to the students' assessment, have a High level in the area of their school development, in which 67.5% demonstrate a High learning achievement and 32.5% a Medium learning achievement, which implies improving and continuing to strengthen the participation of students in school activities to understand what they read at its three levels, thus achieving mixed comprehension. There is a correlation coefficient (r=0.632**; r=0.476**, r=0.630**, 0.502** V Sig. < 0.01) and the research hypothesis can be accepted.